Exploring immune memory traits in the social immunity of a fungus-growing ant - Goes, Aryel C. [UNESP]; Kooij, Pepijn W. [UNESP]; Haifig, Ives; Bueno, Odair C. [UNESP]; Rodrigues, Andre [UNESP] (The Royal Society, 2024)
The immune system is crucial for organisms to defend against pathogens. Likewise, analogous immune features evolved against similar pressures at the superorganism scale. Upregulating hygiene to the same fungus pathogen is one assumption for convergent immune mechanisms in social insects, although more evidence of immune memory features remains to be confirmed. Here, we assess immune memory traits at the colony level in the leaf-cutting ant Atta sexdens. We exposed their fungus cultivar to both homologous and heterologous challenges with the entomopathogenic fungi Metarhizium anisopliae and Beauveria bassiana, as well as the mycoantagonistic fungi Fusarium oxysporum and Trichoderma spirale. By measuring ants' behaviours, we evaluated the capacity of A. sexdens: (i) to enhance their collective hygiene, (ii) speed their hygiene in further infections, (iii) how long this capacity lasts in the colonies and (iv) the degree of specificity to increase hygienic responses. Fungus grooming behaviour was enhanced mostly against entomopathogenic fungi, with a trend of faster reactions during homologous challenges. In general, the capacity to elicit such upregulated actions lasted for up to 30 days, but no longer than 60 days. Overall, colonies exhibited a degree of immune specificity, enhancing hygiene only in response to homologous exposures but decreasing it when infected secondarily with a different fungus, indicating flexible social immunity of A. sexdens after immune challenges.
Keywords: attini ants; hygienic behaviour; immunological memory; pathogens; specificity